A rare coexistence of two gastric outlet obstructive lesions: infantile hypertrophic pyloric stenosis and organoaxial gastric volvulus - Oğuzkurt, Pelin; Şenocak, M. Emin; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 2000)
Infantile pyloric stenosis is one of the most common conditions requiring surgery during the first few weeks of life. The association of infantile pyloric stenosis with gastric volvulus in an extremely uncommon occurrence. A 10-month-old male infant operated for infantile pyloric stenosis at two months of age is presented. His current problem was recurrent pulmonary infections and he was diagnosed to have organoaxial gastric volvulus and gastroesophageal reflux. The common features of presentation, radiological findings, surgical procedures and possible mechanisms of gastric volvulus associated with infantile pyloric stenosis are discussed.
Keywords: gastric volvulus; infantile hypertrophic pyloric stenosis; gastric outlet obstructions